Peran Kontrak Bisnis Dalam Menjamin Kepastian Hukum Dalam Transaksi Jual Beli - Davina Jihan Nur Aini Bayo; Romi Faslah (CV. ITTC INDONESIA, 2025)
Business contracts play a crucial role in ensuring legal certainty in commercial trade transactions. Contracts serve as the legal foundation that clearly and thoroughly defines the rights and obligations of the parties involved, thus preventing ambiguity and potential disputes in the future. With clear and firm contracts, business actors share a common understanding of the agreements made, which substantially reduce the risk of misunderstandings and contract breaches. The legal guarantees provided by contracts also support efficient conflict resolution and offer legal protection for all parties involved. In addition, business contracts encourage business actors to comply with existing regulations and foster trust and stability in commercial relationships. Therefore, business contracts function not onlu as legally binding instruments but also as strategic tools for building a healthy, secure, and sustainable business environment.